Drivers of transformation to competency-based nursing education in Rwanda - Claudine Muraraneza; Ntombifikile Gloria Mtshali (Elsevier, 2020)
Purpose: This article explores the drivers of transformation to competency-based nursing education in Rwanda. Method: The Strauss and Corbin grounded theory approach was used. Ethics approval was obtained prior to data collection. Data were collected using in-depth interviews of academic staff and students, and documents being analyzed using constant comparison. Results: Four categories of transformative factors emerged: (a) the political agenda of the country, (b) the transformation of higher education, (c) the transformation of the health care system and (d) the transformation of undergraduate nursing education. Conclusion: Emerged drivers of nursing education transformation clarify and justify the adoption of a competency-based nursing education program to stakeholders engaged in planning, developing, implementing and evaluating the curriculum to enhance the quality of nursing education in a changing society.